MEMBANGUN KARAKTER ISLAMI ANAK DI PANTI ASUHAN AL-MUSTHOFA MELALUI KEGIATAN MENGAJI, KISAH NABI, PERPUSTAKAAN MINI, DAN POHON HARAPAN - Fasich Nur Firdaus (LPPM STAI Muhammadiyah Probolinggo, 2024)
Abstract Islamic character education plays a crucial role in shaping children's morals, ethics, and behavior, especially for those living in orphanages. Orphaned children often face limitations in access to education and family guidance, making it necessary to implement effective and interactive learning methods to instill Islamic values. This study aims to analyze the effectiveness of Islamic character education programs at Al-Musthofa Orphanage through activities such as communal Quran recitation, listening to prophetic stories, reading books from a mini library, and writing hopes on a